Method for manufacturing image forming material
The production method for image forming materials through depolymerization and polycondensation of polyethylene terephthalate resin with specific diols and acids addresses the limitations of chargeability and durability in toners, achieving improved performance in commercial and industrial printing.
Patent Information
- Application Number
- JP2024103266
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-05
- Filing Date
- 2024-06-26
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2044-06-26
AI Technical Summary
Existing image forming materials used in toners for commercial and industrial printing lack sufficient chargeability, crushability, and scratch resistance, particularly when exposed to shearing and compression, and do not provide a wide fixing width.
A method for producing an image forming material involving the depolymerization of polyethylene terephthalate resin with a diol having 2 to 5 carbon atoms at 180°C to 250°C, followed by polycondensation with an alcohol and carboxylic acid component to create a polyester resin with a high terephthalic acid bishydroxyalkyl ester content, enhancing chargeability and durability.
The resulting image forming material exhibits excellent chargeability, wide fixing width, and scratch resistance, suitable for high-speed printing and durable image quality.
Smart Images

Figure 2025009987000001 
Figure 2025009987000002 
Figure 2025009987000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an imaging material. [Background technology]
[0002] In recent years, with the development of electrophotographic systems, efforts are being made to expand the application of electrophotographic technology to commercial printing, industrial printing, and other applications. In the field of commercial printing and industrial printing, stable high-speed printing is required, so a certain level of low-temperature fixability and hot offset resistance, i.e., a wide fixing width, is required. In addition, it is necessary to have requirements such as durability against shear and compression caused by agitation that the toner experiences in the cartridge so as to prevent the generation of fine powder, and maintaining charging performance in order to stably print a large number of images of the same quality. Image forming materials used in toners and the like have a significant effect on the toner characteristics as described above. Known examples of such materials include polystyrene resins, styrene-acrylic resins, polyester resins, epoxy resins, polyurethane resins, and polyamide resins. Of these, polyester resins have attracted particular attention because they are easy to balance between fixability and chargeability. For example, a toner binder that has excellent fixing and charging properties and contains a polyester resin containing an aliphatic diol having 2 to 4 carbon atoms as a main component has been disclosed (Patent Documents 1 and 2). However, it cannot be said that the toner has sufficient chargeability, wide fixing width, pulverizability, and abrasion resistance to be used in commercial printing and industrial printing, and improvements in these areas are desired. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2018-141966 A [Patent Document 2] Japanese Patent Application Publication No. 9-278873 Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide an image-forming material which is excellent in electrostatic property and pulverizability, has a wide fixing width and has abrasion resistance. [Means for solving the problem]
[0005] The present inventors have made intensive studies and arrived at the present invention. That is, the present invention is a method for producing an image-forming material containing a polyester resin (A) and a colorant, which comprises a step of reacting a polyethylene terephthalate resin (B) with a diol (b) having 2 to 5 carbon atoms at 180°C to 250°C to depolymerize the polyethylene terephthalate resin (B), which contains 60% by weight or more of a bishydroxyalkyl terephthalate ester based on the total weight of the depolymerized product (bx) after the reaction, and a step of polycondensing an alcohol component containing the depolymerized product (bx) and a carboxylic acid component to obtain the polyester resin (A) after the depolymerization step. Effect of the Invention
[0006] According to the present invention, it is possible to provide an image-forming material having excellent electrostatic properties and grindability, a wide fixing width, and abrasion resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The method for producing the image-forming material of the present invention will be described in detail below.
[0008] The method for producing an image-forming material of the present invention includes a step of reacting polyethylene terephthalate resin (B) with diol (b) having 2 to 5 carbon atoms at 180° C. to 250° C. to depolymerize the polyethylene terephthalate resin (B), and a step of obtaining the polyester resin (A) containing 60% by weight or more of a bishydroxyalkyl terephthalate ester based on the total weight of the depolymerized product (bx) after the depolymerization step, by polycondensing an alcohol component containing the depolymerized product (bx) with a carboxylic acid component.
[0009] The image-forming material in the present invention contains a polyester resin (A) obtained by polycondensing an alcohol component containing a depolymerized product (bx) and a carboxylic acid component, and a colorant.
[0010] The polyester resin (A) is a polyester resin obtained by polycondensation of an alcohol component containing a depolymerized product (bx) obtained by reacting a polyethylene terephthalate resin (B) with a diol (b) having 2 to 5 carbon atoms, and a carboxylic acid component.
[0011] The polyethylene terephthalate resin (B) is a polyethylene terephthalate (hereinafter, also referred to as PET) resin, for example, a recycled PET resin, and its raw material is PET products collected from the city (hereinafter, referred to as recycled PET products), such as PET bottles and PET films.
[0012] Examples of the diol (b) having 2 to 5 carbon atoms include ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentyl glycol, neopentyl glycol, diethylene glycol, etc. These may be used alone or in combination of two or more. Of these diols (b) having 2 to 5 carbon atoms, from the viewpoint of low-temperature fixability, ethylene glycol, propylene glycol and neopentyl glycol are preferred, and ethylene glycol is more preferred.
[0013] The present invention includes a step of depolymerizing the polyethylene terephthalate resin (B) by reacting the polyethylene terephthalate resin (B) with a diol (b) having 2 to 5 carbon atoms. The depolymerization step produces a depolymerized product (bx). The depolymerized product (bx) contains a bishydroxyalkyl terephthalate, and may further contain a polyethylene terephthalate oligomer and a polyethylene terephthalate oligomer in which at least one terminal ethylene glycol residue has been replaced with a diol residue having 3 to 5 carbon atoms.
[0014] The depolymerized product (bx) after the reaction contains 60% by weight or more of terephthalic acid bishydroxyalkyl ester based on the total weight of the depolymerized product (bx). The lower limit is preferably 80% by weight, more preferably 90% by weight, and the upper limit is preferably 99.9% by weight, more preferably 99% by weight, and particularly preferably 95% by weight. When the weight ratio of terephthalic acid bishydroxyalkyl ester in the depolymerized product (bx) is less than 60% by weight, the charge retention rate deteriorates.
[0015] The molar ratio of the diol (b) having 2 to 5 carbon atoms to terephthalic acid (diol (b) / terephthalic acid) contained in the depolymerized product (bx) after the reaction (taking into consideration both those contained as a constituent monomer and those contained as a compound) is preferably 2.00 or more, more preferably 2.02 or more, and even more preferably 2.04 or more, from the viewpoint of the charge retention rate, and is preferably 10 or less, more preferably 6 or less, and even more preferably 4 or less, from the viewpoint of removal of excess diol (b) in a post-process. The molar ratio (diol (b) / terephthalic acid) in the depolymerized product (bx) can be calculated from the amount of the diol (b) having 2 to 5 carbon atoms, and the amount of terephthalic acid and ethylene glycol constituting the polyethylene terephthalate resin (B) during the reaction. Specifically, the number of moles of the diol (b) can be calculated as the sum of the number of moles (charge amount / molecular weight) of the diol (b) having 2 to 5 carbon atoms used during the reaction and the number of moles of ethylene glycol constituting the polyethylene terephthalate resin (B) (charge amount of the polyethylene terephthalate resin (B) / 210). The number of moles of terephthalic acid can be calculated as the number of moles of terephthalic acid constituting the polyethylene terephthalate resin (B) (charge amount of the polyethylene terephthalate resin (B) / 210).
[0016] The depolymerization step will now be described. This is a depolymerization step in which a polyethylene terephthalate resin (B) is reacted with a diol (b) having 2 to 5 carbon atoms at 180° C. to 250° C. to obtain a depolymerized product (bx). For example, polyethylene terephthalate resin (B) and diol (b) having 2 to 5 carbon atoms are added, and the esterification reaction apparatus is heated to 180°C to 250°C while stirring, and the diol (b) is depolymerized with respect to the terephthalic acid constituting the polyethylene terephthalate resin (B) at a molar ratio ((b) / terephthalic acid) of 1.0 or more for preferably 0.1 to 30 hours to obtain a depolymerized product (bx). By setting the molar ratio ((b) / terephthalic acid) of diol (b) to terephthalic acid to 1.0 or more under these conditions, it is possible to easily adjust the terephthalic acid bishydroxyalkyl ester to 60% by weight or more based on the total weight of the depolymerized product (bx) after the reaction, which is preferable. If the molar ratio ((b) / terephthalic acid) is less than 1.0, the amount of diol (b) relative to terephthalic acid is reduced, so that the polyethylene terephthalate resin (B) is difficult to depolymerize, and it may be difficult to adjust the terephthalic acid bishydroxyalkyl ester to 60% by weight or more based on the total weight of the depolymerized product (bx) after the reaction. The weight proportion of terephthalic acid bishydroxyalkyl ester contained in the depolymerized product (bx) can be analyzed by using, for example, a liquid chromatograph mass spectrometer. In order to accelerate the progress of the depolymerization step, a known ester catalyst may be added as necessary. In order to melt the polyethylene terephthalate resin and promote the depolymerization reaction, the reaction temperature is preferably 200° C. or more and 250° C. or less, and particularly preferably 220° C. or more and 240° C. or less. If the temperature exceeds 250° C., a thermal decomposition reaction of the depolymerized product (bx) occurs, causing problems in terms of quality such as a low degree of polymerization when polycondensed again. If the temperature is less than 180° C., the depolymerization reaction proceeds slowly, which is a problem in practical production.
[0017] This depolymerized product (bx) can be converted into a polyester diol having a constant degree of polymerization and a stable melt viscosity by controlling the viscosity through re-condensation polymerization, if necessary.
[0018] In the present invention, the polyester resin (A) contains a depolymerized product (bx) as an alcohol component, and may contain a polyol component (x) other than (bx). The polyol component (x) includes a diol (x1) having 2 to 5 carbon atoms, a diol (x2) other than the diol (x1) having 2 to 5 carbon atoms, and a trivalent or higher polyol (x3). These may be used alone or in combination of two or more kinds.
[0019] Examples of the diol (x1) having 2 to 5 carbon atoms include the same as those listed for the diol (b) having 2 to 5 carbon atoms, and preferred examples thereof are also the same.
[0020] Examples of the diol (x2) include alkylene glycols having 6 to 36 carbon atoms (3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, and the like), alkylene ether glycols having 6 to 36 carbon atoms (dipropylene glycol, polyethylene glycol, polypropylene glycol, and the like). Examples of the alkylene oxide adduct include alkylene diols having 6 to 36 carbon atoms (e.g., 1,4-cyclohexanedimethanol and hydrogenated bisphenol A), (poly)alkylene oxide adducts of the above-mentioned alicyclic diols (preferably, the average number of moles added is 1 to 30), aromatic diols [monocyclic dihydric phenols (e.g., hydroquinone, etc.) and bisphenols] and alkylene oxide adducts of the above-mentioned aromatic diols (preferably, the average number of moles added is 2 to 30).
[0021] The alkylene oxide adducts of the bisphenols are obtained by adding alkylene oxide (hereinafter, "alkylene oxide" may be abbreviated as AO) to the bisphenols.
[0022] The bisphenols include those represented by the following general formula (1). HO-Ar-P-Ar-OH (1) [In the formula, P represents an alkylene group having 1 to 3 carbon atoms, -SO2-, -O-, -S- or a direct bond, and Ar represents a phenylene group in which a hydrogen atom may be substituted with a halogen atom or an alkyl group having 1 to 30 carbon atoms.]
[0023] Specific examples of bisphenols include bisphenol A, bisphenol F, bisphenol B, bisphenol AD, bisphenol S, trichlorobisphenol A, tetrachlorobisphenol A, dibromobisphenol F, 2-methylbisphenol A, 2,6-dimethylbisphenol A, and 2,2'-diethylbisphenol F, and two or more of these can be used in combination.
[0024] Examples of the alkylene oxide to be added to the bisphenol include alkylene oxides having 2 to 30 carbon atoms, such as ethylene oxide (hereinafter, "ethylene oxide" may be abbreviated as EO), propylene oxide (hereinafter, "propylene oxide" may be abbreviated as PO), butylene oxide, tetrahydrofuran, and combinations of two or more of these.
[0025] Of these diols (x2), from the viewpoints of low-temperature fixability and heat-resistant storage stability, preferred are alkylene glycols having 6 to 36 carbon atoms and alkylene oxide adducts of aromatic diols, more preferred are alkylene glycols having 6 to 10 carbon atoms and alkylene oxide adducts of bisphenols (average number of moles added is preferably 2 to 5), still more preferred are alkylene glycols having 3 to 6 carbon atoms and alkylene oxide adducts of bisphenol A (average number of moles added is preferably 2 to 5), and particularly preferred are EO and / or PO adducts of bisphenol A (average number of moles added is preferably 2 to 3).
[0026] In addition, the alcohol component constituting the polyester resin (A) preferably contains an alkylene oxide adduct of bisphenol A, and more preferably contains an EO and / or PO adduct of bisphenol A (the average number of moles added is preferably 2 to 3). When the alcohol component constituting the polyester resin (A) contains an alkylene oxide adduct of bisphenol A, the durability of the toner state is improved compared to when it does not contain this adduct.
[0027] Examples of the trivalent or higher polyol (x3) include aliphatic polyhydric alcohols having 3 to 36 carbon atoms and a valence of trivalent or higher, sugars and derivatives thereof, alkylene oxide adducts of aliphatic polyhydric alcohols (average number of moles added is preferably 1 to 30), alkylene oxide adducts of trisphenols (trisphenol PA, etc.) (average number of moles added is preferably 2 to 30), and alkylene oxide adducts of novolak resins (including phenol novolak and cresol novolak, etc., having an average degree of polymerization of preferably 3 to 60) (average number of moles added is preferably 2 to 30).
[0028] Examples of the aliphatic polyhydric alcohol having 3 to 36 carbon atoms and a valence of three or more include alkane polyols and their intramolecular or intermolecular dehydration products, such as glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, sorbitan, polyglycerin, and dipentaerythritol. Furthermore, examples of sugars and their derivatives include sucrose and methyl glucoside.
[0029] Among these trivalent or higher polyols (x3), from the viewpoint of achieving both low-temperature fixing properties and hot offset resistance, preferred are trivalent or higher aliphatic polyhydric alcohols having 3 to 36 carbon atoms, and alkylene oxide adducts (average number of moles added is preferably 2 to 30) of novolak resins (including phenol novolak and cresol novolak, etc., with an average degree of polymerization preferably being 3 to 60), more preferred are trivalent aliphatic polyhydric alcohols having 3 to 8 carbon atoms, and particularly preferred is trimethylolpropane.
[0030] The diol (x2) in the polyol component (x) other than the depolymerized product (bx) constituting the polyester resin (A) is preferably 40 to 100 mol % based on the number of moles of the polyol component (x) other than the depolymerized product (bx). When a diol (x2) and a trihydric or higher polyol (x3) are used in combination as the polyol component (x) other than the depolymerized product (bx) constituting the polyester resin (A), the molar ratio of the diol (x2) to the trihydric or higher polyol (x3), [(x2) / (x3)], is preferably 80 / 20 to 99 / 1, and more preferably 85 / 15 to 98 / 2, from the viewpoint of hot offset resistance.
[0031] Furthermore, the alcohol component constituting the polyester resin (A) may contain a mono-ol component, if necessary. Examples of the mono-ol include linear or branched alkyl alcohols having 1 to 30 carbon atoms (e.g., methanol, ethanol, isopropanol, 1-decanol, dodecyl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, arachidyl alcohol, behenyl alcohol, and lignoceryl alcohol).
[0032] Of these monools, from the viewpoints of image strength and heat-resistant storage stability, linear or branched alkyl alcohols having 8 to 24 carbon atoms are preferred, linear alkyl alcohols having 8 to 24 carbon atoms are more preferred, and dodecyl alcohol, stearyl alcohol, arachidyl alcohol, behenyl alcohol and lignoceryl alcohol are even more preferred.
[0033] In the present invention, examples of the carboxylic acid component constituting the polyester resin (A) include dicarboxylic acid (y1), trivalent or higher polycarboxylic acid (y2), etc. These may be used alone or in combination of two or more.
[0034] Examples of the dicarboxylic acid (y1) include aromatic dicarboxylic acids having 8 to 36 carbon atoms (terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, etc.), aliphatic dicarboxylic acids having 2 to 50 carbon atoms (oxalic acid, malonic acid, succinic acid, adipic acid, oleaginic acid, sebacic acid, etc.), alicyclic dicarboxylic acids having 6 to 40 carbon atoms [dimer acids (dimerized linoleic acid, etc.)], alkene dicarboxylic acids having 4 to 36 carbon atoms (alkenyl succinic acids such as dodecenyl succinic acid, maleic acid, fumaric acid, citraconic acid, mesaconic acid, etc.), and ester-forming derivatives thereof. Here, the ester-forming derivative means carboxylic acid anhydride, alkyl (methyl, ethyl, butyl, stearyl, etc. having 1 to 24 carbon atoms, preferably those having 1 to 4 carbon atoms) esters, and partial alkyl esters.
[0035] Among these dicarboxylic acids (y1), from the viewpoint of achieving both low-temperature fixability, hot offset resistance, and heat-resistant storage stability, preferred are aromatic dicarboxylic acids having 8 to 36 carbon atoms, aliphatic dicarboxylic acids having 2 to 50 carbon atoms, and alkene dicarboxylic acids having 4 to 36 carbon atoms, more preferred are terephthalic acid, isophthalic acid, adipic acid, succinic acid, maleic acid, and fumaric acid, particularly preferred are terephthalic acid, isophthalic acid, adipic acid, fumaric acid, and succinic acid, and most preferred are terephthalic acid, isophthalic acid, adipic acid, and succinic acid. In addition, anhydrides or lower alkyl esters of these acids may be used.
[0036] Examples of the trivalent or higher polycarboxylic acid (y2) include trivalent or higher aromatic polycarboxylic acids having 9 to 20 carbon atoms (such as trimellitic acid and pyromellitic acid), aliphatic (including alicyclic) tricarboxylic acids having 6 to 36 carbon atoms (such as hexanetricarboxylic acid and decanetricarboxylic acid), and ester-forming derivatives thereof.
[0037] Among these trivalent or higher polycarboxylic acids (y2), from the viewpoint of achieving both low-temperature fixability and hot offset resistance, aromatic polycarboxylic acids having 9 to 20 carbon atoms are preferred, and trimellitic acid and pyromellitic acid are more preferred. In addition, anhydrides and lower alkyl esters of these acids may also be used.
[0038] Furthermore, as the carboxylic acid component constituting the polyester resin (A), a monocarboxylic acid component may be contained, if necessary. Examples of the monocarboxylic acid include aromatic monocarboxylic acids having 7 to 37 carbon atoms (benzoic acid, toluic acid, 4-ethylbenzoic acid, 4-propylbenzoic acid, etc.), and aliphatic (including alicyclic) monocarboxylic acids having 2 to 50 carbon atoms (acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, pelargonic acid, capric acid, lauric acid, myristic acid, palmitic acid, margaric acid, stearic acid, behenic acid, etc.).
[0039] Among these monocarboxylic acids, aromatic monocarboxylic acids having 7 to 37 carbon atoms are preferred, and benzoic acid is more preferred, from the viewpoints of image strength and heat-resistant storage stability.
[0040] The acid value of the polyester resin (A) is preferably from 0 to 50 mgKOH / g, and more preferably from 0.1 to 30 mgKOH / g, from the viewpoints of low-temperature fixability, charge retention rate, and durability of print quality. The acid value can be measured by the method specified in JIS K0070.
[0041] The glass transition temperature of the polyester resin (A) is preferably from 50 to 75°C, and more preferably from 55 to 70°C, from the viewpoints of heat-resistant storage stability and low-temperature fixability. The glass transition temperature (Tg) of the polyester resin (A) can be determined by the method (DSC method) specified in ASTM D3418-82. For example, DSC Q20 manufactured by TA Instruments Co., Ltd. can be used to measure the glass transition temperature (Tg). The glass transition temperature (Tg) can be measured under the following conditions. <Measurement conditions> (1) Heat from 30°C to 150°C at 20°C / min (2) Hold at 150°C for 10 minutes (3) Cool to -35°C at 20°C / min (4) Keep at -35°C for 10 minutes (5) Heat up to 150°C at 20°C / min. (6) The differential scanning calorimetry curve measured in the process of (5) is analyzed, and the position of the inflection point is determined as the glass transition temperature.
[0042] From the viewpoints of low-temperature fixability, heat-resistant storage stability, and crushability, the peak top molecular weight of the polyester resin (A) is preferably from 3,000 to 100,000, and more preferably from 5,000 to 50,000.
[0043] In the present invention, the weight average molecular weight and the peak top molecular weight can be measured by gel permeation chromatography (GPC) under the following conditions. Equipment (example): Tosoh Corporation HLC-8120 Column (example): 2 TSK GEL GMH6 [Tosoh Corporation] Measurement temperature: 40℃ Sample solution: 0.25% by weight in THF Solution injection volume: 100μL Detector: Refractive index detector Reference material: 12 standard polystyrenes (TSKstandard POLYSTYRENE) manufactured by Tosoh Corporation (molecular weight: 500, 1,050, 2,800, 5,970, 9,100, 18,100, 37,900, 96,400, 190,000, 355,000, 1,090,000, 2,890,000) For measuring the molecular weight, a sample is dissolved in tetrahydrofuran (THF) to a concentration of 0.25% by weight, and the insoluble matter is filtered off using a PTFE filter with an aperture of 220 nm to obtain a sample solution.
[0044] The process for obtaining the polyester resin (A) will be described. The polyester resin (A) can be obtained by carrying out a polycondensation reaction between an alcohol component containing the depolymerized product (bx) and a carboxylic acid component in the presence of a polymerization catalyst.
[0045] Specifically, the polyester resin (A) can be produced, for example, as follows: For example, an alcohol component containing the depolymerized product (bx) and a carboxylic acid component are subjected to a polycondensation reaction in an inert gas (nitrogen gas, etc.) atmosphere at a reaction temperature of preferably 150 to 280°C, more preferably 160 to 250°C, and even more preferably 170 to 235°C.
[0046] In this case, an esterification catalyst can be used as necessary. Examples of the esterification catalyst include tin-containing catalysts (e.g., dibutyltin oxide, etc.), antimony trioxide, titanium-containing catalysts [e.g., titanium alkoxides (tetrabutoxytitanate, etc.), potassium oxalate titanate, titanium terephthalate, titanium alkoxide terephthalate, catalysts described in JP-A-2006-243715 {titanium diisopropoxybis(triethanolaminate), titanium dihydroxybis(triethanolaminate), titanium monohydroxytris(triethanolaminate), titanyl bis(triethanolaminate) and their intramolecular polycondensates, etc.} and catalysts described in JP-A-2007-11307 (titanium tributoxyterephthalate, titanium triisopropoxyterephthalate, titanium diisopropoxyditerephthalate, etc.)], zirconium-containing catalysts (e.g., zirconyl acetate, etc.) and zinc acetate, etc. Among these, titanium-containing catalysts are preferred.
[0047] In order to stably proceed with the polymerization of the polyester, a stabilizer may be added, such as hydroquinone, methylhydroquinone, and a hindered phenol compound.
[0048] The image-forming material in the present invention may contain, in addition to the polyester resin (A), resins such as vinyl resins, epoxy resins, polyurethane resins, polycarbonate resins, crystalline polyester resins, and crystalline vinyl resins.
[0049] When the image-forming material of the present invention contains a resin other than the polyester resin (A), the weight proportion of the polyester resin (A) is preferably 10% by weight or more, and more preferably 20% by weight or more, based on the total weight of the resins (100% by weight), from the viewpoint of the fixing width of the toner. Furthermore, the weight proportion of resins other than the polyester resin (A) is preferably 90% by weight or less, and more preferably 80% by weight or less, based on the total weight of the resins (100% by weight), from the viewpoint of the fixing width of the toner. The weight proportion of the polyester resin (A) in the image-forming material is preferably 10 to 90% by weight, more preferably 10 to 87% by weight, even more preferably 20 to 76% by weight, and particularly preferably 25 to 68% by weight, based on the weight of the image-forming material, from the viewpoint of the fixing width of the toner. The weight proportion of resins other than the polyester resin (A) in the image-forming material is preferably 10 to 90% by weight, more preferably 10 to 87% by weight, even more preferably 20 to 76% by weight, and particularly preferably 25 to 65% by weight, based on the weight of the image-forming material, from the viewpoint of the fixing width of the toner. The weight proportion of the resin including the polyester resin (A) in the image-forming material is preferably 30 to 97% by weight, more preferably 40 to 95% by weight, and even more preferably 45 to 92% by weight, based on the weight of the image-forming material, from the viewpoint of the fixing width of the toner.
[0050] The image forming material in the present invention contains a colorant.
[0051] As the colorant, all of the dyes and pigments used as toner colorants can be used. For example, carbon black, iron black, Sudan Black SM, Fast Yellow G, Benzidine Yellow, Pigment Yellow, India Fast Orange, Irgasin Red, Paranitroaniline Red, Toluidine Red, Carmine FB, Pigment Orange R, Lake Red 2G, Rhodamine FB, Rhodamine B Lake, Methyl Violet B Lake, Phthalocyanine Blue, Pigment Blue, Brilliant Green, Phthalocyanine Green, Oil Yellow GG, Kayaset YG, Orazol Brown B, and Oil Pink OP can be mentioned. The colorant may be any one of these alone or a mixture of two or more. In addition, if necessary, magnetic powder (powder of ferromagnetic metals such as iron, cobalt, and nickel, or compounds such as magnetite, hematite, and ferrite) can be contained to function as a colorant.
[0052] The image-forming material in the present invention may contain, in addition to the colorant, one or more known additives selected from a release agent, a charge control agent, a fluidizing agent, and the like, if necessary.
[0053] Examples of the release agent include aliphatic hydrocarbon waxes such as low molecular weight polypropylene, low molecular weight polyethylene, low molecular weight polypropylene-polyethylene copolymers, polyolefin wax, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax, and oxides thereof; carnauba wax, montan wax, sazol wax, and deacidified waxes thereof; ester waxes such as fatty acid ester wax; fatty acid amides; fatty acids; higher alcohols; fatty acid metal salts; and mixtures thereof.
[0054] Examples of polyolefin waxes include (co)polymers of olefins (e.g., ethylene, propylene, 1-butene, isobutylene, 1-hexene, 1-dodecene, 1-octadecene, and mixtures thereof) [including those obtained by (co)polymerization and thermally degradable polyolefins], oxides of olefin (co)polymers with oxygen and / or ozone, maleic acid modified products of olefin (co)polymers [e.g., products modified with maleic acid and its derivatives (maleic anhydride, monomethyl maleate, monobutyl maleate, dimethyl maleate, etc.)], copolymers of olefins and unsaturated carboxylic acids [(meth)acrylic acid, itaconic acid, maleic anhydride, etc.] and / or unsaturated carboxylic acid alkyl esters [(meth)acrylic acid alkyl (C1-18 alkyl) esters and maleic acid alkyl (C1-18 alkyl) esters, etc.], and Sasol wax.
[0055] The higher alcohol is an aliphatic alcohol having 30 to 50 carbon atoms, for example, triacontanol. The fatty acid is an aliphatic alcohol having 30 to 50 carbon atoms, for example, triacontanol.
[0056] Examples of the charge control agent include nigrosine dyes, triphenylmethane dyes containing a tertiary amine as a side chain, quaternary ammonium salts, polyamine resins, imidazole derivatives, polymers containing a quaternary ammonium base, metal-containing azo dyes, copper phthalocyanine dyes, metal salicylic acid salts, boron complexes of benzilic acid, sulfonic acid group-containing polymers, fluorine-containing polymers, and halogen-substituted aromatic ring-containing polymers. A specific example of the charge control agent is T-77 (azo-based iron complex manufactured by Hodogaya Chemical Co., Ltd.).
[0057] Examples of the fluidizing agent include colloidal silica, alumina powder, and titanium oxide powder.
[0058] The content of the colorant is preferably from 0.05 to 60% by weight, more preferably from 0.1 to 55% by weight, and even more preferably from 0.5 to 50% by weight, based on the weight of the image-forming material. The content of the releasing agent is preferably from 0 to 30% by weight, more preferably from 0.5 to 20% by weight, and further preferably from 1 to 10% by weight, based on the weight of the image-forming material. The content of the charge control agent is preferably 0 to 20% by weight, more preferably 0.1 to 10% by weight, and further preferably 0.5 to 7.5% by weight, based on the weight of the image forming material. The content of the fluidizing agent is preferably from 0 to 10% by weight, more preferably from 0 to 5% by weight, and even more preferably from 0.1 to 4% by weight, based on the weight of the image-forming material. The total content of the additives is preferably from 3 to 70% by weight, more preferably from 4 to 58% by weight, and even more preferably from 5 to 50% by weight, based on the weight of the image-forming material. By setting the composition ratio of the image-forming material within the above range, it is possible to easily obtain an image-forming material that has good low-temperature fixing properties, hot offset resistance, chargeability (charge retention rate), durability of print quality, and durability of the image-forming material.
[0059] The image-forming material may be obtained by any of the known methods such as a kneading / pulverizing method, an emulsion phase inversion method, and a polymerization method. For example, when an image-forming material is obtained by a kneading and pulverizing method, the components constituting the image-forming material except for the fluidizing agent are dry-blended, melt-kneaded, coarsely pulverized, and finally, pulverized using a jet mill pulverizer or the like, and further classified to obtain fine particles having a volume average particle size (D50) of preferably 5 to 20 μm, and then the fluidizing agent is mixed therein to produce the image-forming material. The volume average particle size (D50) is measured using a Coulter counter {for example, trade name: Multisizer III [manufactured by Beckman Coulter, Inc.]}.
[0060] In addition, when the image-forming material is obtained by the emulsion phase inversion method, the components constituting the image-forming material except for the fluidizing agent are dissolved or dispersed in an organic solvent, and then emulsified by adding water or the like, and then, if necessary, subjected to aggregation or the like, and then separated and classified to produce the image-forming material. The volume average particle size of the image-forming material is preferably 3 to 15 μm.
[0061] In the case of toner applications, the toner is mixed with carrier particles such as iron powder, glass beads, nickel powder, ferrite, magnetite, and ferrite coated with resin (acrylic resin, silicone resin, etc.) as necessary to be used as a developer for electric latent images. When carrier particles are used, the weight ratio of the toner to the carrier particles is preferably 1 / 99 to 99 / 1. Also, the toner can be rubbed against a member such as a charging blade instead of the carrier particles to form an electric latent image. The toner does not necessarily need to contain carrier particles.
[0062] The image forming material is fixed to a support (paper, polyester film, etc.) by a copier, printer, etc. to form a recording material. As a method for fixing to a support, a known heat roll fixing method, flash fixing method, etc. can be used.
[0063] The image forming material is used for developing electrostatic images or magnetic latent images in electrophotography, electrostatic recording, electrostatic printing, etc. More specifically, it is used for developing electrostatic images or magnetic latent images particularly suitable for full color.
[0064] The present specification discloses the following:
[0065] The present disclosure (1) is a method for producing an image-forming material containing a polyester resin (A) and a colorant, the method comprising the steps of reacting a polyethylene terephthalate resin (B) with a diol (b) having 2 to 5 carbon atoms at 180°C to 250°C to depolymerize the polyethylene terephthalate resin (B), which contains 60% by weight or more of a bishydroxyalkyl terephthalate ester based on the total weight of a depolymerized product (bx) after the reaction, and polycondensing an alcohol component containing the depolymerized product (bx) with a carboxylic acid component to obtain the polyester resin (A) after the depolymerization step.
[0066] The present disclosure (2) is a method for producing an image-forming material according to the present disclosure 1, in which the alcohol component of the polyester resin (A) contains an alkylene oxide adduct of bisphenol A.
[0067] The present disclosure (3) is a method for producing an image-forming material according to the present disclosure (1) or (2), in which the carboxylic acid component of the polyester resin (A) contains isophthalic acid.
[0068] The present disclosure (4) relates to a method for producing an image-forming material according to any one of the present disclosures (1) to (3), wherein the weight proportion of the polyester resin (A) is 10 to 90% by weight based on the weight of the image-forming material.
[0069] The present disclosure (5) is the method for producing an image-forming material according to any one of the present disclosures (1) to (4), wherein the polyethylene terephthalate resin (B) is a recycled PET resin. EXAMPLES
[0070] The present invention will be further described below with reference to examples and comparative examples, but the present invention is not limited to these.
[0071] <Production Example 1> Synthesis of polyester resin (A1) 170 parts by weight (2.74 parts by mole) of ethylene glycol and 556 parts by weight of recovered PET resin (2.65 parts by mole of each of the constituent monomers terephthalic acid and ethylene glycol) were placed in a pressurizable reaction vessel, and a depolymerization reaction (closed transesterification reaction) was carried out at 220°C for 2 hours with stirring to obtain a depolymerized product after the reaction. Liquid chromatography mass spectrometry revealed that the depolymerized product contained 90% by weight of terephthalic acid bishydroxyalkyl ester. Next, 726 parts by weight of the depolymerized product was cooled to 180°C, and 478 parts by weight of bisphenol A·PO 2-mol adduct and 1 part by weight of tetrabutoxytitanate as a condensation catalyst were added. The mixture was heated to 220°C while being depressurized at a reduced pressure of 0.5 to 2.5 kPa to remove ethylene glycol, and when the peak top molecular weight reached 6700, it was cooled to 175°C. Next, 15 parts by weight of trimellitic anhydride was added, and esterification was carried out at normal pressure for 1 hour at 175°C, and then the mixture was taken out to obtain polyester resin (A1). 230 parts by weight of ethylene glycol was recovered by distillation.
[0072] <Production Example 2> Synthesis of polyester resin (A2) The depolymerization reaction was carried out in the same manner as in Production Example 1, except that the raw materials and reaction temperature shown in Table 1 were used, and a depolymerized product was obtained after the reaction. Next, 954 parts by weight of the depolymerized product was cooled to 180°C, and 281 parts by weight of isophthalic acid and 1 part by weight of tetrabutoxy titanate as a condensation catalyst were added, and while heating to 220°C, the pressure was reduced under a reduced pressure of 0.5 to 2.5 kPa to remove ethylene glycol and water, and when the peak top molecular weight reached 7800, the mixture was cooled to 175°C. Next, 15 parts by weight of trimellitic anhydride was added, and esterification was performed at normal pressure at 175°C for 1 hour, and then the mixture was taken out to obtain polyester resin (A2). The amount of ethylene glycol recovered by distillation was 191 parts by weight.
[0073] <Production Example 3> Synthesis of polyester resin (A3) The depolymerization reaction was carried out in the same manner as in Production Example 1, except that the raw materials and reaction temperature shown in Table 1 were used, and a depolymerized product was obtained after the reaction. Next, 726 parts by weight of the depolymerized product was cooled to 180°C, and 478 parts by weight of bisphenol A·PO 2-mol adduct and 1 part by weight of tetrabutoxytitanate as a condensation catalyst were added. The mixture was heated to 220°C while being depressurized at a reduced pressure of 0.5 to 2.5 kPa to remove ethylene glycol, and when the peak top molecular weight reached 6400, it was cooled to 175°C. Next, 15 parts by weight of trimellitic anhydride was added, and esterification was carried out at normal pressure for 1 hour at 175°C, and then the mixture was taken out to obtain polyester resin (A3). 230 parts by weight of ethylene glycol was recovered by distillation.
[0074] <Production Example 4> Synthesis of polyester resin (A4) The depolymerization reaction was carried out in the same manner as in Production Example 1, except that the raw materials and reaction temperature shown in Table 1 were used, and a depolymerized product was obtained after the reaction. Next, 726 parts by weight of the depolymerized product was cooled to 180°C, and 478 parts by weight of bisphenol A·PO 2-mol adduct and 1 part by weight of tetrabutoxytitanate as a condensation catalyst were added. The mixture was heated to 220°C while being depressurized at a reduced pressure of 0.5 to 2.5 kPa to remove ethylene glycol, and when the peak top molecular weight reached 7100, it was cooled to 175°C. Next, 15 parts by weight of trimellitic anhydride was added, and esterification was carried out at normal pressure for 1 hour at 175°C, after which the polyester resin (A4) was obtained by removal of the ethylene glycol. 230 parts by weight was recovered by distillation.
[0075] Comparative Production Example 1 Synthesis of Polyester Resin (A'1) In a pressurizable reaction vessel, 170 parts by weight of ethylene glycol, 478 parts by weight of bisphenol A·PO 2-mol adduct, and 556 parts by weight of recovered PET resin were placed and reacted for 15 hours under a nitrogen stream at 200°C while stirring and distilling off ethylene glycol, then reacted under reduced pressure of 2.5-5.0 kPa, and cooled to 175°C when the weight average molecular weight (Mw) reached 6800. Next, 15 parts by weight of trimellitic anhydride was placed and esterified at normal pressure for 1 hour at 175°C, after which the polyester resin (A'1) was obtained by removal. The amount of ethylene glycol recovered by distillation was 230 parts by weight.
[0076] Comparative Production Example 2: Synthesis of polyester resin (A'2) The depolymerization reaction was carried out in the same manner as in Production Example 1, except that the raw materials and reaction temperature shown in Table 1 were used, and a depolymerized product was obtained after the reaction. Next, 726 parts by weight of the depolymerized product was heated to 180°C, and 478 parts by weight of bisphenol A·PO 2-mol adduct and 1 part by weight of tetrabutoxytitanate as a condensation catalyst were added. The mixture was heated to 220°C while being depressurized at a reduced pressure of 0.5 to 2.5 kPa to remove ethylene glycol, and when the peak top molecular weight reached 7400, it was cooled to 175°C. Next, 15 parts by weight of trimellitic anhydride was added, and esterification was carried out at normal pressure for 1 hour at 175°C, and then the mixture was taken out to obtain polyester resin (A'2). 230 parts by weight of ethylene glycol was recovered by distillation.
[0077] [Table 1]
[0078] <Production Example 5> Synthesis of polyester resin (C1) In a reaction vessel, 140 parts by weight of bisphenol A·PO 2-mol adduct, 600 parts by weight of bisphenol A·PO 3-mol adduct, 32 parts by weight of trimethylolpropane, 176 parts by weight of terephthalic acid, 17 parts by weight of trimellitic anhydride, and 1 part by weight of tetrabutoxy titanate as a condensation catalyst were placed, and the mixture was reacted for 4 hours at 220°C under a nitrogen stream while distilling off the water produced, and then reacted for 2 hours under a reduced pressure of 0.5 to 2.5 kPa. Then, 90 parts by weight of trimellitic anhydride was added at 210°C, and the mixture was reacted for 1 hour under normal pressure, and then reacted for 10 hours under a reduced pressure of 0.5 to 5 kPa, and then taken out. The obtained resin was cooled to room temperature, crushed, and granulated to obtain polyester resin (C1). The physical properties of polyester resin (C1) are shown in Table 2.
[0079] <Production Example 6> Synthesis of polyester resin (C2) In a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen inlet tube, 715 parts by weight of propylene glycol, 740 parts by weight of terephthalic acid, 35 parts by weight of adipic acid, and 1 part by weight of tetrabutoxy titanate as a polymerization catalyst were placed and reacted for 12 hours under nitrogen flow at 180°C while distilling off the water generated. The temperature was then gradually increased to 230°C, and the reaction was continued for 4 hours under nitrogen flow while removing the water generated, and the reaction was continued under reduced pressure of 0.7 to 2.7 kPa, and the reaction was cooled when the softening point reached 88°C. The amount of propylene glycol recovered was 325 parts by weight. The reaction was then cooled to 180°C, and 50 parts by weight of trimellitic anhydride was added, and the reaction was continued for 2 hours under sealed conditions, after which the reaction was continued at 220°C under reduced pressure of 2.7 to 5.3 kPa and the reaction was taken out at a predetermined softening point. The resin obtained was cooled to room temperature, pulverized and granulated to obtain polyester resin (C2). The physical properties of polyester resin (C2) are shown in Table 2.
[0080] [Table 2]
[0081] <Examples 1 to 4> Using a Henschel mixer [FM10B manufactured by Mitsui Miike Chemical Engineering Co., Ltd.], polyester resin (A) and polyester resin (C) as toner binders were premixed with colorants, release agents, and charge control agents according to the compounding ratios (parts by weight) in Table 3, and then kneaded with a twin-screw kneader [PCM-30 manufactured by Ikegai Corporation]. Then, after finely pulverizing using a supersonic jet pulverizer Labjet [manufactured by Nippon Pneumatic Industrial Co., Ltd.], the mixture was classified with an air classifier [MDS-I manufactured by Nippon Pneumatic Industrial Co., Ltd.] to obtain toner particles with a particle size D50 of 7 μm. Next, 0.5 parts by weight of colloidal silica [Aerosil R972: manufactured by Nippon Aerosil Co., Ltd.] was mixed with 100 parts by weight of the toner particles using a sample mill to obtain toners (T1) to (T4) as image forming materials.
[0082] <Comparative Examples 1 to 2> Using a Henschel mixer [FM10B manufactured by Mitsui Miike Chemical Engineering Co., Ltd.], comparative polyester resin (A') and polyester resin (C) as toner binders were premixed with colorants, release agents, and charge control agents according to the compounding ratios (parts by weight) in Table 3, and then kneaded with a twin-screw kneader [PCM-30 manufactured by Ikegai Corporation]. Then, after finely pulverizing using a supersonic jet pulverizer Labjet [manufactured by Nippon Pneumatic Industrial Co., Ltd.], the mixture was classified with an air classifier [MDS-I manufactured by Nippon Pneumatic Industrial Co., Ltd.] to obtain toner particles with a particle size D50 of 7 μm. Next, 0.5 parts by weight of colloidal silica [Aerosil R972: manufactured by Nippon Aerosil Co., Ltd.] was mixed with 100 parts by weight of the toner particles using a sample mill to obtain toners (T'1) to (T'2) as image forming materials.
[0083] [Table 3]
[0084] The colorants, release agents, and charge control agents in Table 3 are as follows: Colorant: Carbon black MA-100 [Mitsubishi Chemical Co., Ltd.] Release agent: Carnauba wax [manufactured by Toyo Adle Co., Ltd.] Charge control agent: T-77 [Hodogaya Chemical Co., Ltd.]
[0085] [Evaluation method] <Charge retention rate> (1) 0.5 g of toner and 20 g of ferrite carrier (F-150, manufactured by Powder Tech Co., Ltd.) were placed in a 50 mL glass bottle, and the bottle was conditioned at 23° C. and a relative humidity of 50% for 8 hours or more. (2) The mixture was stirred by friction at 50 rpm for 10 minutes and 60 minutes using a Turbulent Shaker Mixer, and the charge amount after each time was measured using a blow-off charge amount measuring device (manufactured by Kyocera Chemical Corporation). Using the obtained values, "charge amount after 60 minutes of friction / charge amount after 10 minutes of friction" was calculated, and this was taken as the charge stability index. A larger charge stability index indicates a more excellent charge retention rate. Under these evaluation conditions, a charge stability index of 0.8 or more is preferable.
[0086] <Fixing width> Toner is applied to the paper at 1.00 mg / cm 2 The powder was evenly applied so that the surface was uniform. The method of applying the powder to the paper surface at this time was to use a printer without a thermal fixing device. The paper was passed through a soft roller at a fixing speed (circumferential speed of the heating roller) of 213 mm / sec and at a heating roller temperature range of 90 to 230°C in 5°C increments. Next, the presence or absence of cold offset in the fixed image was visually observed, and the temperature at which cold offset occurred (MFT) and the temperature at which hot offset occurred were measured. The difference between the low temperature fixing temperature and the hot offset resistance temperature was taken as the fixing width. The wider the fixing width, the better the toner is. In this evaluation condition, a temperature of 80° C. or higher is preferable.
[0087] <Crushability> To 85 parts by weight of each of the toner binders used in the toners (T1) to (T4) and (T'1) to (T'2), 8 parts by weight of the pigment carbon black MA-100 [manufactured by Mitsubishi Chemical Corporation], 4 parts by weight of the release agent carnauba wax, and 2 parts by weight of the charge control agent T-77 [manufactured by Hodogaya Chemical Industry Co., Ltd.] were added, and the mixture was premixed using a Henschel mixer [FM10B manufactured by Mitsui Miike Chemical Engineering Co., Ltd.], and then kneaded using a twin-screw kneader [PCM-30 manufactured by Ikegai Corporation]. The mixture was cooled and then pulverized and classified to sizes of 8.6 mesh pass to 30 mesh on to be used as particles for evaluating pulverizability. These particles for evaluating pulverizability were finely pulverized using a supersonic jet pulverizer Labojet [manufactured by Nippon Pneumatic Mfg. Co., Ltd.] under the following conditions. Crushing pressure: 0.5MPa Grinding time: 10 minutes Adjuster ring: 15mm Louver size: Medium The finely ground particles for evaluating grindability were not classified, and the volume average particle size (μm) of the finely ground particles was measured using a Coulter Counter TAII (manufactured by Coulter Electronics, Inc., USA), and the grindability was evaluated according to the following criteria. Under these conditions, it is preferable for the particle size to be less than 7 μm.
[0088] <Abrasion resistance> The image fixed at 150°C used in the measurement of the fixing width was used as a test piece to carry out an abrasion resistance test using a Gakushin type abrasion fastness tester. The image was rubbed back and forth 50 times with a rubbing element attached to a 60mm x 60mm cotton cloth (Kanakin No. 3) under a load of 100g. The image retention rate was determined visually from the fixed image after the test, and the abrasion resistance of the toner was evaluated according to the following criteria. ◎: Image retention rate is 70-100% ○: Image retention rate is 50-69% ×: Image remaining rate is less than 50% In this evaluation, a rating of ⊚ or higher is desirable. [Industrial Applicability]
[0089] The image-forming material of the present invention has excellent chargeability, a wide fixing width, and excellent pulverizability and abrasion resistance, and therefore can be suitably used as a toner for developing electrostatic images in electrophotography, electrostatic recording, electrostatic printing, etc. Furthermore, it can be suitably used for inkjet printing and as a surface modifier for recording media.
Claims
1. A method for producing an image-forming material containing a polyester resin (A) and a colorant, the method comprising the steps of reacting a polyethylene terephthalate resin (B) with a diol (b) having 2 to 5 carbon atoms at 180° C. to 250° C. to depolymerize the polyethylene terephthalate resin (B), and obtaining the polyester resin (A) by polycondensing an alcohol component containing the depolymerized product (bx) and a carboxylic acid component after the depolymerization step, the polyester resin (A) containing 60% by weight or more of a bishydroxyalkyl terephthalate ester based on a total weight of the depolymerized product (bx) after the depolymerization step.
2. 2. The method for producing an image-forming material according to claim 1, wherein the alcohol component of the polyester resin (A) contains an alkylene oxide adduct of bisphenol A.
3. 3. The method for producing an image-forming material according to claim 1, wherein the carboxylic acid component of the polyester resin (A) contains isophthalic acid.
4. 3. The method for producing an image-forming material according to claim 1, wherein the weight ratio of the polyester resin (A) is 10 to 90% by weight based on the weight of the image-forming material.
5. 3. The method for producing an image-forming material according to claim 1, wherein the polyethylene terephthalate resin (B) is a recycled PET resin.
Citation Information
Patent Citations
Polyester resin for electrostatic charge image developing toner and method of manufacturing the same, electrostatic charge image developing toner and method of manufacturing the same, electrostatic charge image developer, image forming method, and image forming device
JP2009192856A
Toner binder and toner
JP2023010575A
Magnetic powder composition
JP2023028717A
Polyester resin for toner
JP1997278873A
Toner binder and toner
JP2018141966A